2002
DOI: 10.1080/09638180220124770
|View full text |Cite
|
Sign up to set email alerts
|

Financial accounting developments in the European Union: past events and future prospects

Abstract: The decision of the Commission of the European Union (EU) to oblige listed European companies, from 2005 onwards, to establish their consolidated financial statements according to IFRS (IAS) represents a preliminary peak in the internationalization process of financial accounting in Europe. The purpose of this paper is to highlight the landmarks of accounting developments in the EU since the Fourth and Seventh Directives and to reveal the obvious internationalization process of financial accounting in the EU, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
20

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(75 citation statements)
references
References 44 publications
1
54
0
20
Order By: Relevance
“…At the same time, the internationalization of capital markets, and particularly the increasing centrality of US stock exchanges for global capital flows, gave American accounting rules (US GAAP) a global reach and FASB, the American standard-setter, and the SEC more leverage in international standard-setting (Haller 2002). Both agencies viewed US GAAP as superior to IAS in terms of coherence and transparency, and they were not ready to list foreign companies on US stock exchanges unless these fulfilled the reporting requirements defined in US GAAP.…”
Section: Path Generation In the Transnational Void: Setting Internatimentioning
confidence: 99%
“…At the same time, the internationalization of capital markets, and particularly the increasing centrality of US stock exchanges for global capital flows, gave American accounting rules (US GAAP) a global reach and FASB, the American standard-setter, and the SEC more leverage in international standard-setting (Haller 2002). Both agencies viewed US GAAP as superior to IAS in terms of coherence and transparency, and they were not ready to list foreign companies on US stock exchanges unless these fulfilled the reporting requirements defined in US GAAP.…”
Section: Path Generation In the Transnational Void: Setting Internatimentioning
confidence: 99%
“…Additionally, there are certain countries where the IFRS has replaced local accounting legislations in a specific manner. Such inconsistent expectations regarding when and how the IFRS should be applied makes financial reporting difficult to compare between industries [10]. Table 4 Summary of use of IFRS in some European countries [4] From the survey, we highlight the case in Slovenia and Bulgaria, where the IFRS has been imposed for all types of financial statements, including stand-alone statements of private companies.…”
Section: Ifrs Presence In Europementioning
confidence: 99%
“…Haller (2002) considers that there is no way for the harmonization of accounting rules. Jermakowicz et al (2007) showed that the majority of German companies that used IAS/IFRS did it only for the preparation of their consolidated financial statements.…”
Section: The Complexity Of Some Rules and Accounting Treatmentsmentioning
confidence: 99%